Human Enhancement Technologies as a New Factor of Social Inequality in Modern Society - Sinyavskaya, Oxana; Biryukova, Svetlana; Selezneva, Elena (Journal of Economic Sociology, 2025)
The concept of “human enhancement” describes the process by which innate human abilities are temporarily or permanently enhanced using various technologies and their combinations. Such technologies include information and communication technologies (ICT), biomedical, neurocognitive, nanotechnology, as well as social and humanitarian technologies. This review focuses on the social consequences of the development of human enhancement technologies. Its main questions are: what does the available research say about how the emergence of human enhancement technologies affects social inequality? Does it expand opportunities for lower social groups or, on the contrary, strengthen the positions of the upper ones? The article opens with a discussion on conceptual issues of the relationship between human enhancement technologies, inequality, and social exclusion. Then, using case studies of three groups of technologies, namely cognitive enhancement, assisted reproductive technologies, and life extension technologies (biogenetic and biogerontological), the authors consider, on the one hand, the opportunities for increasing well-being and reducing social exclusion, and, on the other, the risks that arise in connection with the development of human enhancement technologies. This leads to a discussion on the challenges for social policy that arise from the relationship between the development of human enhancement technologies, social exclusion, and inequality, and on possible responses to these challenges. A review of the literature devoted to the effects of human enhancement technologies showed that a significant portion of empirical publications are presented in medical journals. Their number is still small, but even fewer studies are devoted to the socio-economic aspects of the use of enhancement technologies. Scientific discourse on the social consequences of the use of human enhancement technologies is still largely theoretical and speculative, and the available scattered empirical evidence more often points to the reproduction and strengthening of existing socio-economic inequality and its translation into socio-biological inequality, although the conclusions are still far from unambiguous and sustainable.